Analysis of Understanding of Handball Game Rules among STKIP Pasundan UKM Members - Irzi Atmaka; Yopi Meirizal; Rama Adha Septiana (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the level of understanding of the members of the STKIP Pasundan Handball Student Activity Unit (UKM) regarding the rules of handball. The method used in this study is a quantitative descriptive method. The subjects in this study were 20 active members of the STKIP Pasundan Handball Student Activity Unit. The data collection technique was carried out using a closed questionnaire consisting of 25 multiple-choice questions about the rules of handball. Each correct answer was scored 1 point, so that the total maximum score was 25 points. The results showed that of the 20 respondents, 2 people (10%) had a level of understanding in the Good category, 13 people (65%) in the Sufficient category, and 5 people (25%) in the Poor category. There were no respondents in the Very Poor and Very Good categories. Thus, it can be concluded that the majority of the STKIP Pasundan Handball Student Activity Unit members have a sufficient understanding of the rules of handball. These findings are expected to be used as evaluation material and consideration for UKM administrators and the campus to continue to improve the quality of members' understanding through training or ongoing coaching activities